Legal Protection of Bonds in Bankruptcy - Saputro, Vincentius Saryo; Samuel, Andrew Nicholas; Wirayudha, Michael Jordan (Kertha Patrika, 2026)
This study examines legal protection mechanisms for bondholders during issuer bankruptcy through a comparative analysis of Indonesian and US frameworks. Indonesian regulations—including the Capital Market Law, Bankruptcy and Suspension of Payment Law, and trustee provisions—demonstrate significant gaps in protecting bondholder claims during insolvency proceedings. Conversely, the US system, anchored by the Trust Indenture Act of 1939 and Chapter 11 Bankruptcy Code, provides superior protection through creditors’ committees, cramdown provisions, and fiduciary duty shifts that ensure both substantive and procedural safeguards. Key findings reveal Indonesia’s regulatory deficiencies in claim prioritization, trustee empowerment, and bondholder representation in bankruptcy proceedings. This research proposes US-model reforms to strengthen investor protection, enhance market credibility, and promote economic stability in Indonesia’s capital market.